Simultaneous electrochemical determination of uric acid and hypoxanthine at a TiO2/graphene quantum dot-modified electrode - Ngoc Hoang, Vu; Hoa, Dang Thi Ngoc; Quang Man, Nguyen; Son, Le Vu Truong; Son, Le Van Thanh; Nguyen, Vo Thang; Phong, Le Thi Hong; Diem, Ly Hoang; Ly, Kieu Chan; Thang, Ho Sy; Quang Khieu, Dinh (Beilstein Journal of Nanotechnology, 2024)
A TiO2/graphene quantum dots composite (TiO2/GQDs) obtained by in situ synthesis of GQDs, derived from coffee grounds, and peroxo titanium complexes was used as electrode modifier in the simultaneous electrochemical determination of uric acid and hypoxanthine. The TiO2/GQDs material was characterized by photoluminescence, X-ray diffraction, Raman spectroscopy, high-resolution transmission electron microscopy, and energy-dispersive X-ray mapping. The TiO2/GQDs-GCE exhibits better electrochemical activity for uric acid and hypoxanthine than GQDs/GCE or TiO2/GCE in differential pulse voltammetry (DPV) measurements. Under optimized conditions, the calibration plots were linear in the range from 1.00 to 15.26 μM for both uric acid and hypoxanthine. The limits of detection of this method were 0.58 and 0.68 μM for uric acid and hypoxanthine, respectively. The proposed DPV method was employed to determine uric acid and hypoxanthine in urine samples with acceptable recovery rates.
Keywords: graphene quantum dots; hypoxanthine; peroxo titanium complexes; uric acid